Adherence to Direct Oral Anticoagulants in Patients With Non-Valvular Atrial Fibrillation: A Cross-National Comparison in Six European Countries (2008–2015) - Sabaté, M.; Vidal, X.; Ballarin, E.; Rottenkolber, M.; Schmiedl, S.; Grave, B.; Huerta, C.; Martin-Merino, E.; Montero, D.; Leon-Muñoz, L. M.; Gasse, C.; Moore, N.; et al. (Frontiers in Pharmacology, 2021)
Aims: To describe and compare the adherence to different direct oral anticoagulants (DOACs) in 8 European databases representing 6 countries. Methods: Longitudinal drug utilization study of new users (≥18 years) of DOACs (dabigatran, rivaroxaban, apixaban) with a diagnosis of non-valvular atrial fibrillation (2008-2015). Adherence was examined by estimating persistence, switching and discontinuation rates at 12 months. Primary non-adherence was estimated in BIFAP and SIDIAP databases. Results: The highest persistence rate was seen for apixaban in the CPRD database (81%) and the lowest for dabigatran in the Mondriaan database (22%). The switching rate for all DOACs ranged from 2.4% to 13.1% (Mondriaan and EGB databases respectively). Dabigatran had the highest switching rate from 5.0 % to 20.0% (Mondriaan and EGB databases, respectively). The discontinuation rate for all DOACs ranged from 16.0% to 63.9% (CPRD and Bavarian CD databases, respectively). Dabigatran had the highest rate of discontinuers, except in the Bavarian CD and AOK Nordwest databases, ranging from 23.2% to 64.6% (CPRD and Mondriaan databases, respectively). Combined primary non-adherence for examined DOACs was 11.1% in BIFAP and 14.0% in SIDIAP. There were differences in population coverage and in the type of drug data source among the databases. Conclusion: Despite the differences in the characteristics of the databases and in demographic, and baseline characteristics of the included population that could explain some of the observed discrepancies, we can observe a similar pattern throughtout the databases. Apixaban was the DOAC with the highest persistence. Dabigatran had the highest proportion of discontinuers and switchers at 12 months in most databases.. (EMA/2015/27/PH).